ACHIEVING AN HONEST RECONCILIATION: ISLAMIC AND INTERNATIONAL HUMANITARIAN LAW - Fajri Matahati Muhammadin (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2015)
The compatibility between Islamic law and international law has been a long lasting source of both academic discussion and social friction. This includes the Islamic laws on conduct of war (IsHL), especially in context of the Middle East conflicts. This article explores how there are two extreme opinions: ‘Islamophobes’ and apologists –both of them being dishonest. It will be shown that there are multi-level possibilities of relations between IsHL and International Humanitarian Law including possible incompatibilities, and that an ijma is a good room for reconciliation. Kompatibilitas hukum Islam dan hukum internasional telah lama menjadi sumber debat akademis dan friksi social. Termasuk diantaranya adalah hukum Islam terkait pelaksanaan perang, terutama di tengah konflik Timur Tengah seperti sekarang. Artikel ini mengamati dua pendapat ekstrim: ‘Islamofobik’ dan ‘apologist’ –keduanya tidak jujur. Akan ditunjukan ada berbagai tingkat kemunginan hubungan antara hukum perang Islam dan Hukum Humaniter Internasional, termasuk diantaranya adalah kemungkinan pertentangan, lalu bagaimana dibutuhkan sebuah ijma untuk menyelesaikan masalah tersebut.